Testing a prediction model for the H-mode density pedestal against JET-ILW pedestals. (1st May 2023) - Saarelma, S.; Connor, J.W.; Bilkova, P.; Bohm, P.; Field, A.R.; Frassinetti, L.; Fridstrom, R.; Kirk, A.; ,
Abstract: The neutral ionisation model proposed by Groebner et al (2002 Phys. Plasmas 9 2134) to determine the plasma density profile in the H-mode pedestal, is extended to include charge exchange processes in the pedestal stimulated by the ideas of Mahdavi et al (2003 Phys. Plasmas 10 3984). The model is then tested against JET H-mode pedestal data, both in a 'standalone' version using experimental temperature profiles and also by incorporating it in the Europed version of EPED. The model is able to predict the density pedestal over a wide range of conditions with good accuracy. It is also able to predict the experimentally observed isotope effect on the density pedestal that eludes simpler neutral ionization models.